"All still quiet on the non-Western front?" Non-Western public service motivation scholarship: 2015–2020. Issue 1 (2nd January 2021) - Mussagulova, Assel; van der Wal, Zeger
Abstract : Public service motivation (PSM) scholarship has mushroomed since the early 2000s. After initially being an exclusively Western field of study, scholarship has recently become more internationalised. As a corollary, scholars have begun to formulate a research agenda for advancing non-Western PSM research. To contribute to this advancement, and examine how non-Western PSM scholarship has developed in recent years, we conduct a systematic literature review of 83 empirical studies published between 2015 and 2020. We assess origin of scholarship, theories, samples and methodologies used, and empirical findings on the relation between PSM and key antecedents and outcomes. Our findings show that non-Western PSM scholarship is growing, and increasingly using contextual variables to explain variance in findings in comparison with Western studies. That being said, ample opportunity remains for leveraging contextual and regional particularities to build a more distinct body of scholarship. We conclude with suggestions for further advancing non-Western PSM research.